Congratulations John Grant!. (30th March 2016) - Artyushkova, Kateryna
Abstract : With this special issue, we are celebrating the outstanding career of John Grant, who is retiring from both his roles as SIA North‐American Editor and his affiliation with the University of Dayton Research Institute and the Air Force Materials Lab. We open this issue with a personal note from the Air Force Research Laboratory written by Neil Murphy. This note is followed by an essay by several of John's surface analysis colleagues, highlighting the professionalism that has been one of the hallmarks of John's career. We are all indebted to John for conveying the importance of true professionalism through his teaching, journal editorship and numerous other contributions to the surface analysis community. John's many professional activities and awards are summarized below.